Bureaucrats First.: The Leading Role of Policymakers in the Dutch Neoliberal Turn of the 1980s. - Oudenampsen, Merijn; Mellink, Bram (TSEG - The Low Countries Journal of Social and Economic History, 2021)
In the 1980s, a fundamental shift took place in Dutch economic policy: Keynesian demand-management was exchanged for a neoliberal supply-side approach. The single most influential account of this transformation has focused on consensus among corporatist policymakers as key to the reforms. It is the origin story of the Dutch ‘polder model’. The problem however, is that there is surprisingly little evidence for corporatist consensus in the 1980s. Instead of consensus, we argue that there has been a conflict of ideas between Keynesians and supply-siders. And instead of corporatism, we point to bureaucratic elites as a crucial factor in the Dutch policy shift. From the mid-1970s onwards, an influential group of senior public officials emerged that successfully advocated for a supply-side policy, inspired by the industrialization policies developed in the 1950s. In so doing, we believe the Dutch case exemplifies the pathbreaking role of administrative elites as highlighted by Skocpol, Weir and Heclo, rather than corporatist consensus.